The widely occurring brittlestar Ophiactis savignyi (Amphilepidida: Ophiactidae) as an epibiont on loggerhead sea turtle, Caretta caretta - Hayashi, Ryota; Okanishi, Masanori (Zootaxa, 2019)
We describe the first occurrence of the widely occurring brittlestar Ophiactis savignyi (Müller & Troschel, 1842) as epibionts on Caretta caretta (Linnaeus, 1758), the loggerhead sea turtles. On the sea turtle epibionts, the coronulid barnacles were well studied as listed in Hayashi (2013), and recently some crustaceans were collected from loggerhead sea turtles and described as new species (Tanabe et al. 2017; Tanaka and Hayashi 2019). In contrast, echinoderm epibionts listed from sea turtles are poorly understood (Table 1) and this study represents the novel discovery of an ophiuroid, which was not previously known to occur on the surface of this species.